Penguatan Pengetahuan Peternak Mengenai Kesehatan Hewan Melalui Pemeriksaan Kondisi Fisiologis di Peternakan Domba Mega Mulya, Pangandaran - Wulansari, Asri; Ismiraj, Muhammad Rifqi; Mayasari, Novi; Firmansyah, Indra (Fakultas Pertanian, 2024)
This community service aimed to enhance farmers' knowledge of sheep health through physiological condition assessments and environmental monitoring at Mega Mulya Sheep Farm, Pangandaran. With a tropical-oceanic climate, the region poses challenges related to heat stress, impacting livestock productivity. Farmers were trained in evaluating environmental conditions, calculating the Temperature-Humidity Index (THI), and measuring physiological parameters such as heart rate, respiratory rate, rectal temperature, and sweating rate. Practical sessions introduced the use of tools like stethoscopes, digital thermometers, and cobalt chloride discs for sweat rate assessment. Results showed that while the physiological conditions of the sheep remained within normal ranges, THI indicated moderate heat stress during midday. This activity equipped farmers with practical knowledge to manage environmental and physiological factors, ensuring optimal productivity and animal welfare.